Faktor-Faktor yang Mempengaruhi Kejadian Hipertensi pada Ibu Hamil Di Rumah Sakit Umum Aliyah Kota Kendari Tahun 2022 - Siahaan, Avris Romario Diparaja; Veronika, Erna; Shorayasari, Susi; Nurmawaty, Dwi (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2023)
Hypertension is a manifestation of disturbances in the hemodynamics of the High blood pressure in pregnancy can reduce blood flow to the placenta, which will affect the supply of oxygen and nutrients to the baby. This can slow the growth of the baby and increase the risk during delivery. Pregnancy Hypertension ranks as the ninth disease at Aliyah Kendari Hospital with a prevalence that increases every year, namely 13% in 2019, 15.2% in 2020, 14% in 2021, and 15.5% in 2022 which has an impact on increasing miscarriage in the first trimester and sudden fetal death (stillbirth). This study aims to determine the factors associated with hypertension in pregnant women at the hospital. Aliyah Kendari City. This research was conducted at Aliyah Hospital, Kendari City in 2022. The research was conducted with a cross-sectional design. The population in this study were pregnant women at Aliyah Hospital, Kendari City during January-June 2022. The sampling technique used a random sampling system, namely by randomizing the patient's medical record number. The type of data in this study used secondary data from medical record data January-June 2022 by collecting data using form sheets and checklist sheets. Data analysis technique using chi-square analysis. Based on the bivariate analysis, it showed that there was a significant relationship between age (p value = 0.000, PR = 3.020), obesity (p value = 0.000, PR = 8.718), family history of hypertension (p value = 0.000, PR = 2.918), parity (p value = 0.000, PR = 2.181), working mother status (p value = 0.003, PR = 1.358). The suggestion of this research is that hospitals can further improve education about hypertension in pregnancy.